PEMERIKSAAN REFRAKSI SUBYEKTIF PADA PENDERITA PRESBYOPIA DENGAN STATUS REFRAKSI EMMETROPIA - Imam Setyana; Nensi Mesrani Tarigan; Opep Cahya Nugraha (Akademi Refraksi Optisi dan Optometry Gapopin, 2020)
Abstract Accomodation is a mechanism that regulates the focus of the eyes to respond to visual stimulation by changing the refractive power of the crystaline lens. To focus near object, the cilliary muscle contracts which changes the shapes of the lens. However with increasing age, elasticity of the lens decreases causing anomalies of accomodation called presbyopia. The teatment of presbyopia is the prescription of appropriate convex glasses for near work. In this paper, the writer uses descriptive methods from the library data regarding subjective refraction to find the correction lens diopters to reach the best visual acuity. Keywords: Pattern, Single Vision Sphero Cylinder Lenses, Descriptive, Accurate, Quality